Teaching 'Proper' Drinking? Clubs and pubs in Indigenous Australia - Brady, Maggie (ANU Press, 2017)
"In Teaching 'Proper' Drinking?, the author brings together three fields of scholarship: socio-historical studies of alcohol, Australian Indigenous policy history and social enterprise studies. The case studies in the book offer the first detailed surveys of efforts to teach responsible drinking practices to Aboriginal people by installing canteens in remote communities, and of the purchase of public hotels by Indigenous groups in attempts both to control sales of alcohol and to create social enterprises by redistributing profits for the community good. Ethnographies of the hotels are examined through the analytical lens of the Swedish 'Gothenburg' system of municipal hotel ownership. The research reveals that the community governance of such social enterprises is not purely a matter of good administration or compliance with the relevant liquor legislation. Their administration is imbued with the additional challenges posed by political contestation, both within and beyond the communities concerned. 'The idea that community or government ownership and management of a hotel or other drinking place would be a good way to control drinking and limit harm has been commonplace in many Anglophone and Nordic countries, but has been less recognised in Australia. Maggie Brady's book brings together the hidden history of such ideas and initiatives in Australia ... In an original and wide-ranging set of case studies, Brady shows that success in reducing harm has varied between communities, largely depending on whether motivations to raise revenue or to reduce harm are in control.' - Professor Robin Room, Director, Centre for Alcohol Policy Research, La Trobe University"